2017
DOI: 10.1002/app.45659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemically modified clinoptilolite on the thermal, morphological, and gas separation properties of mixed matrix membranes

Abstract: Mixed matrix membranes (MMM) based on polysulfone and chemically modified clinoptilolite were prepared. Clinoptilolite enriched with Ca2+, K+, and Na+ by ion exchange at two test temperatures was prepared. Chemical composition was monitored by energy dispersive X‐ray spectroscopy. X‐ray diffraction, thermogravimetric analysis, and N2 adsorption–desorption isotherms were also performed. Thermal and morphological properties of MMM were evaluated. CH4/CO2 gas mixture permeability tests at different upstream press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Even though the experimental performance of MMMs did not overcome the performance for the pair of gases CO 2 /CH 4 reported in the literature, it is noteworthy the addition of 10 wt % of clinoptilolite impregnated with EA and BHPA represented an important approach to the upper bound. In addition, a comparison of the performance of some polysulfone‐based MMMs reported recently, and the MMMs reported in this work are listed in Table S1 . It could be seen that modified clinoptilolite could be considered as a good candidate to be used as filler in MMM to improve the CO 2 permeability and CO 2 /CH 4 selectivity.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Even though the experimental performance of MMMs did not overcome the performance for the pair of gases CO 2 /CH 4 reported in the literature, it is noteworthy the addition of 10 wt % of clinoptilolite impregnated with EA and BHPA represented an important approach to the upper bound. In addition, a comparison of the performance of some polysulfone‐based MMMs reported recently, and the MMMs reported in this work are listed in Table S1 . It could be seen that modified clinoptilolite could be considered as a good candidate to be used as filler in MMM to improve the CO 2 permeability and CO 2 /CH 4 selectivity.…”
Section: Resultsmentioning
confidence: 81%
“…A customized mixed‐gas permeation apparatus previously reported elsewhere was used for the gas permeability measurements using a gas mixture of CH 4 and CO 2 (molar percentage 95/5). The two‐part permeation cell (upstream side and downstream side) is made of 316 stainless steel, where the membrane is located between them supported onto a porous ceramic disk.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability system was previously described and reported. [28][29] The upstream side was pressurized to 50, 150, and 300 psi of feed gas mixture with a solenoid valve and determined with equipment pressure detector, additionally, has a downstream section with a pressure detector. This section was at atmospheric pressure (14.7 psi) using Helium as carrier gas.…”
Section: Permeation Measurements Of Binary (N 2 /Ch 4 ) and Ternarymentioning
confidence: 99%
“…It is observed that the permeability in all cases decreases as the pressure increasing, this is attributed to the compression effect that compacts and reduces the free volume in the membranes. 26,28,30 Additionally, Table 1 shows the permeability results in the binary mixed gas N 2 /CH 4 , where is observed that N 2 permeability of MMMs with modified zeolite (3.7 barrer) increase two-fold in regard to the pristine membrane (1.22 barrer). However, in the ternary gas mixture CO 2 /N 2 /CH 4 , the permeability of N 2 in the pristine membrane is close to the MMMs (PBI-CLINOn and PBI-CLINOm) 1.26, 1.46, and 1.29 barrer, respectively.…”
Section: Characterization Of Polymeric Membranes and Mixed Matrix Mmentioning
confidence: 99%